2015
DOI: 10.1016/j.cell.2015.03.052
|View full text |Cite
|
Sign up to set email alerts
|

Structural Snapshots of Actively Translating Human Ribosomes

Abstract: Summary Macromolecular machines, such as the ribosome, undergo large-scale conformational changes during their functional cycles. While their mode of action is often compared to that of mechanical machines, a crucial difference is that at the molecular dimension, thermodynamic effects dominate functional cycles, with proteins fluctuating stochastically between functional states defined by energetic minima on an energy landscape. Here, we have used cryo-electron microscopy to image ex vivo-derived human polysom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

28
257
4

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(289 citation statements)
references
References 85 publications
28
257
4
Order By: Relevance
“…6, Video 1), it may be assumed that the dissociation of deacylated tRNA from the E-site of the PRE complex should result in translocation in the forward direction. Recently, a structural study has shown that the dissociation occurs upon binding of a complex of eEF2 and GTP, which stabilises the rotated conformation of the PRE ribosome that is incompatible with deacylated tRNA in the E site (46). This also agrees with a recent kinetic study, in which dissociation has been observed prior to the formation of the POST complex (44).…”
Section: Discussionsupporting
confidence: 84%
“…6, Video 1), it may be assumed that the dissociation of deacylated tRNA from the E-site of the PRE complex should result in translocation in the forward direction. Recently, a structural study has shown that the dissociation occurs upon binding of a complex of eEF2 and GTP, which stabilises the rotated conformation of the PRE ribosome that is incompatible with deacylated tRNA in the E site (46). This also agrees with a recent kinetic study, in which dissociation has been observed prior to the formation of the POST complex (44).…”
Section: Discussionsupporting
confidence: 84%
“…The present demonstration of two proofreading steps during mRNA translation on the bacterial ribosome resonates with recent cryo-EM data of translating ribosomes directly prepared from live human cells (20). Spahn and coworkers (20) identified a ribosome complex containing aa-tRNA in A/T state with eEF1α in the GDP conformation, where domains II and III were ordered, maintaining the interaction with the tRNA T-stem, while the G domain was disordered. This complex was about equally populated as a preaccommodation complex without eEF1α with aa-tRNA in similar position.…”
Section: Outlook: Are There Also Two Proofreading Steps In Eukaryote supporting
confidence: 85%
“…We suggest that multistep proofreading in genetic code translation has evolved to neutralize potential error hot spots originating in error-prone initial selection of aa-tRNA in ternary complex with EF-Tu and GTP (18,19). Recent cryo-EM data of ribosomes from live human cells show two states of ribosome-bound preaccommodated aa-tRNA, one with aa-tRNA in complex with the EF-Tu homolog eEF1α in the GDP form, the other with only aa-tRNA after release of eEF1α·GDP (20). With support from these cryo-EM data in conjunction with the present findings, we suggest that two-step proofreading mechanisms are at work not only in bacteria but also in eukaryotes and, perhaps, in all three kingdoms of life.…”
mentioning
confidence: 99%
“…RNAs like the ribosome and some aptamer domains of riboswitches have largely preformed secondary structure but transit through multiple states as they fold or transit through their functional cycles (see e.g. Baird et al 2010a, b;Behrmann et al 2015;Das et al 2003;Noller, 2005). For most RNAs with this property, however, it is unclear if tertiary structures are retained throughout the conformational cycle.…”
Section: Preformed Tertiary Contacts In Heterogeneous States With Mohmentioning
confidence: 99%
“…Nevertheless, analogous sequencing approaches of comparable complexity are being developed and numerous groups have recognized steps to bring the methods onto a quantitative footing (Eddy, 2014;Konig et al 2011;Kwok et al 2015). Excitingly, rich microscopy data becoming available for actively translating ribosomes (Behrmann et al 2015) will provide gold standard data to test MXM before its in vivo application to RNA messages, long non-coding RNAs, and viral genomes that will be difficult to probe with other methods.…”
Section: Additional Advantages But Multiple Stepsmentioning
confidence: 99%